2021
DOI: 10.1126/scitranslmed.abl4097
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of immune selection in intact and defective proviruses distinguish HIV-1 elite controllers

Abstract: Increasing evidence suggests that durable drug-free control of HIV-1 replication is enabled by effective cellular immune responses that may induce an attenuated viral reservoir configuration with a weaker ability to drive viral rebound. Here, we comprehensively tracked effects of antiviral immune responses on intact and defective proviral sequences from elite controllers (ECs), analyzing both classical escape mutations and HIV-1 chromosomal integration sites as biomarkers of antiviral immune selection pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 74 publications
4
64
0
Order By: Relevance
“…Therefore, viral control could account for an interplay between virus infectiveness and immune response which is conceivable to be more efficient against viruses that bear non-functional Envs, showing poor fusion and infection capacities and very limited evolution, characteristics that we observed in viral Envs from LTNP phenotypes, as shown recently ( Lian et al, 2021 ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, viral control could account for an interplay between virus infectiveness and immune response which is conceivable to be more efficient against viruses that bear non-functional Envs, showing poor fusion and infection capacities and very limited evolution, characteristics that we observed in viral Envs from LTNP phenotypes, as shown recently ( Lian et al, 2021 ).…”
Section: Discussionsupporting
confidence: 73%
“…The immune response has recently been proposed to be related to the control of viral evolution by potentially removing functional evolved viruses from ECs, but these viruses would resist immune-mediated elimination through chromosomal integration into heterochromatin locations conferring deep latency and protecting against immune targeting ( Lian et al, 2021 ). The authors argued that these immune events are not fundamentally different between individuals under antiretroviral therapy (ART) and ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, residual HIV reservoirs still exist when cART is initiated during primary HIV infection in adults 87 . To date, few HIV-infected individuals remain healthy without treatment, in which long-term treatment pressure may drive proviruses to accumulate in human inactive gene regions of host chromosomes, likely stymieing new virus production 88 , 89 . It is reported that prophylactic broadly neutralizing antibody (bnAb) therapy given at 30 h or cART regimen at 48 h in one-month-old macaques after oral exposure to low pathogenic SHIVSF162P3 90 , 91 could clear tissue viral reservoirs 92 , 93 , in which all animals show aviremic outcomes over time even at initiation of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the persistent provirus population varies among individuals and the mechanisms that determine if a proviral genome is capable of reactivation remain inadequately understood. Studies of CD4+ T cells from individuals who naturally control HIV-1 infection demonstrated that intact proviruses are enriched in heterochromatic regions of the host genome while defective proviruses are detected in euchromatic regions [ 19 , 33 ]. These observations support that enhanced immune detection and clearance in these individuals shapes the persistent provirus reservoir over time, relegating intact proviruses to relatively silent loci of the host genome [ 34 ].…”
Section: Defective Hiv-1 Genomes Dominate the Proviral Landscapementioning
confidence: 99%
“…Immunological selection and clonal expansion of cells harboring HIV proviral genomes shapes the persistent reservoir [ 24 , 33 , 46 , 106 , 107 ]. For example, cells that express HIV-1 generate MHC-I associated peptides that are targeted and eliminated by CD8+ T cells.…”
Section: Defective Viruses Immune Dysfunction and Cure Strategiesmentioning
confidence: 99%